Understanding the Obligation of Learning for Students (Analysis of Surah Al-A'raf, verse 172) - Abdul Aziz Romdhoni (Values: Jurnal Kajian Islam Multidisiplin, 2025)
The Qur'an contains several verses about students, discussing the nature of students, their development, and their religious development. From this discussion, it can be seen that Surah Al-Taubah, verse 122, discusses the nature of students, Surah Al-Hadid, verse 20, and Surah Al-A'raf, verse 172, discusses their religious development. From the above explanation, it can be concluded that the description of student characteristics in the Qur'an and Hadith is related to the explanation of scientific concepts. This is evidenced by the mutually reinforcing explanations between the characteristics contained in the Qur'an, Hadith, and the concept of developmental psychology.